9 ECV and T1 mapping in repaired tetralogy of fallot – CMR diffuse fibrosis measurement needs the right method for the right ventricle?. (May 2018) - Ghonim, Sarah; Jenkins, Sophie; Smith, Gillian C; Mathew, George; Gatzoulis, Michael A; Gatehouse, Peter; Babu-Narayan, Sonya V
Abstract : Introduction: It is increasingly appreciated applying parametric mapping to the RV has inherent challenges. Methods: We studied native LV and RV T1 mapping and ECV measures at 1.5 T in repaired tetralogy of Fallot (rTOF) patients (n=44, 24 male, 32±14 years, 35 (80%), NYHA class I). Single slices targeted perpendicular to to the LV septum or RV inferior wall using 11HB-MOLLI (6 mm slice thickness/TR 279 ms/TE 1.1 ms/Flip-angle 35 ° ). Like image planes were repeated using 'high sensitivity native T1' 14HB-MOLLI (6 mm slice thickness/TR 300 ms/TE 1.1 ms/Flip-angle 5°) in attempt to improve sensitivity to tissue collagen. Haematocrit for ECV calculation was obtained within a few hours of CMR. Results: RVECV correlated with LVECV (r=0.7; p<0.001). Nineteen (46%) had increased RVECV (>35%) and 3 (8%) increased LVECV (>30%). Associations with all standard risk factors in rTOF were tested. RVECV correlated with right atrial area, (r=0.4; p<0.05). 'High-sensitivity native T1' correlated with akinetic RVOT length (r=0.6; p<0.05), and left atrial area (r=0.3; p=0.07) and QRS duration (r=0.3; p=0.4). RVECV did not correlate with high-sensitivity' native T1. No diffuse RV fibrosis measure correlated with ejection fraction. Conclusion: Diffuse fibrosis was only associated with increased right atrial and RVOT akinetic area size which if true may relate to RV diastolic dysfunction. Given the lack of consistency of findings between techniques more data are needed, including determination of how the measures obtained relate to myocardial composition. Despite best efforts to obtain optimum RV T1 maps these findings suggest current approaches have limited use and dedicated RV sequence development is required.